Changes in Academic Ethics – Remarks on the Margin - Woroniecka, Grażyna (Roczniki Nauk Społecznych, 2023)
In the article I discuss the concept of The University in ruins by Bill Readings. I briefly present the changes that have taken place in universities in Poland in the sphere of ethical orientations towards institutional transformations. I analyze the possibilities of preserving the value of the didactic process in the conditions of teaching commodification, and I also examine the effects of the “logic of accountability” for research and scientific advancement. I put forward the thesis that the “discourse of excellence”, which makes the university a kind of bureaucratic-capitalist enterprise, causes the formation of a new moral code of academic staff – not yet written down, but already noticeable.